The Mediating Impact of Organisational Commitment and Job Satisfaction on Lecturer Performance in the Workplace Spirituality - Usep Suherman; Herry Sutanto (UIN Sunan Gunung Djati, 2024)
This study aims to investigate the influence of spirituality in the workplace on instructor performance and organisational commitment. Furthermore, it seeks to examine the impact of job satisfaction on the performance of lecturers and their level of commitment to the organisation. Moreover, it seeks to investigate the role of organisational commitment in mediating the connection between spirituality in the workplace and professor performance, as well as its role in mediating the relationship between job happiness and lecturer performance. This study utilises a quantitative method by employing a questionnaire. This study encompassed a group of lecturers from PTKIS in the West Java Region, with a total of 498 individuals. A research study was conducted by selecting a sample of 250 lecturers from PTKIS in the West Java Region. The researchers obtained primary data for this study by distributing questionnaires to lecturers from the West Java Region PTKIS. The sample technique employed is purposive sampling. Meanwhile, The methodology utilised for data analysis is structural equation modelling (SEM) with the implementation of a partial least squares (PLS) approach. The results of the study indicate that the inclusion of spirituality in the academic setting positively influences the academic performance of instructors. Integrating spirituality in the workplace yields a beneficial impact on the level of dedication and loyalty employees have towards the firm. Job happiness positively impacts lecturer performance. Moreover, work satisfaction exerts a beneficial impact on organizational commitment. Organizational commitment positively impacts lecturer performance. Subsequent research findings indicate that organizational commitment acts as a mediator between spirituality in the workplace and lecturer performance. Organizational commitment acts as a mediator between work happiness and lecturer performance.